Tax Education and Social Norms Shape Taxpayer Compliance in Indonesia: Pendidikan Pajak dan Norma Sosial Mempengaruhi Kepatuhan Wajib Pajak di Indonesia - Jordan, Mikail Nabil; Mulyadi, Akhmad (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Tax compliance remains a central concern in sustaining national fiscal stability and achieving revenue targets. Specific Background: In Indonesia, despite continuous reform and education efforts, voluntary tax compliance among individual taxpayers remains suboptimal, particularly within regional tax offices such as KPP Pratama Sidoarjo Utara. Knowledge Gap: Previous studies have not sufficiently integrated the behavioral dimensions of social norms and religiosity alongside tax education in explaining compliance variations. Aims: This study aims to examine how tax education, social norms, and religiosity collectively shape taxpayer compliance. Results: Using a quantitative method and multiple linear regression on data from 150 respondents, findings reveal that tax education and social norms significantly enhance compliance, while religiosity shows no statistical significance. Novelty: The study uniquely integrates the Theory of Planned Behavior with religious and sociocultural constructs to explain compliance patterns in an Indonesian context. Implications: Strengthening educational strategies and fostering positive social norms may serve as more effective tools for improving compliance than relying solely on moral-religious appeals. Highlights: Tax education and social norms significantly shape compliance behavior. Religiusity shows a non-significant relationship with compliance. Behavioral-based approaches outperform moral-based strategies in taxation. Keywords: Tax Education; Social Norms; Religiosity; Taxpayer Compliance; Behavioral Economics